2013
DOI: 10.2522/ptj.20120454
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Mini-Balance Evaluation Systems Test (Mini-BESTest) in Community-Dwelling Individuals With Chronic Stroke

Abstract: The Mini-BESTest is a reliable and valid tool for evaluating balance in people with chronic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
178
9
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(234 citation statements)
references
References 54 publications
33
178
9
6
Order By: Relevance
“…Single‐leg‐standing on the paretic side (item 3) was very challenging for majority of individuals with stroke, regardless of whether they were users of assistive device or not. Indeed, a previous study found that this task has a severe floor effect in individuals with chronic stroke (Tsang et al., 2013). There was also a lack of significant between‐group difference for item 7 (standing on foam with eyes closed).…”
Section: Discussionmentioning
confidence: 99%
“…Single‐leg‐standing on the paretic side (item 3) was very challenging for majority of individuals with stroke, regardless of whether they were users of assistive device or not. Indeed, a previous study found that this task has a severe floor effect in individuals with chronic stroke (Tsang et al., 2013). There was also a lack of significant between‐group difference for item 7 (standing on foam with eyes closed).…”
Section: Discussionmentioning
confidence: 99%
“…The MiniBESTest is the only measure among 26 common balance measures for community-dwelling people that incorporates almost all contents of balance, such as static and dynamic body stability, transfers, gait, variation of support surfaces, variation of visual conditions, obstacle negotiation, external forces and dual-tasking (Di Carlo et al, 2016;Franchignoni et al, 2010;Pardasaney et al, 2013). The Mini-BESTest appears to gain ground in neurological assessment as it reveals a lower ceiling effect compared to BBS (Godi et al, 2013;King et al, 2012); robust psychometric properties especially for Parkinson and stroke populations (Dahl and Jørgensen, 2014;Duncan et al, 2013;King et al, 2012;Leddy, Crowner, and Earhart, 2011;Mak and Auyeung, 2013;Tsang, Liao, Chung, and Pang, 2013) and a broad range of activities along the entire spectrum of task and environment complexity (Pardasaney et al, 2013). A further advantage of the Mini-BESTest is that its total score can now be transformed from ordinal summed raw scores into internal-level measurements using a specific nomogram, created recently by Franchignoni et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Being characterized as one of the most comprehensive balance measures for community-dwelling adults and elderly individuals (O'Hoski, Sibley, Brooks, and Beauchamp, 2015;Pardasaney et al, 2013); together with its excellent reliability (Godi et al, 2013;Leddy, Crowner, and Earhart, 2011;Padgett, Jacobs, and Kasser, 2012;Tsang, Liao, Chung, and Pang, 2013) and validity properties (Bergström, Lenholm, and Franzen, 2012;Franchignoni et al, 2010;King et al, 2012;Tsang, Liao, Chung, and Pang, 2013), the Mini-BESTest could be one of the preferred means of international balance assessments for stroke patients who present balance impairments in any of the following domains: static and dynamic body stability; transfers and gait. Its utility into the Greek clinical environment is now achievable as an official adaptation of the Mini-BESTest into Greek has been performed (Lampropoulou et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The 14 items are scored from 0 (severe impairment) to 2 (normal function) to represent anticipatory balance, reactive postural control, sensory orientation, and dynamic gait functions. Interrater reliability is above 0.96 for the total score on the Mini-BESTest [32]. The TUG is an item of the Mini-BESTest and was used to assess functional mobility [32].…”
Section: Measurementsmentioning
confidence: 99%
“…Interrater reliability is above 0.96 for the total score on the Mini-BESTest [32]. The TUG is an item of the Mini-BESTest and was used to assess functional mobility [32]. Two force-sensitive resistors (FSRs) (Interlink Electronics Inc; Camarillo, California) were positioned under the heel and medial forefoot of each foot to determine stance and swing phases of the gait cycle.…”
Section: Measurementsmentioning
confidence: 99%